Pengaruh suplementasi tablet fe mingguan dan harian terhadap kepatuhan minum tablet Fe dan perubahan kadar hemoglobin pada ibu hamil di Kabupaten Bantul Yogyakarta - Dwi Susetyo; Mohammad Hakimi; Hamam Hadi (Jurnal Gizi Klinik Indonesia, 2005)
Background: In Indonesia, in 1995, 50.9% pregnant women suffer from Iron Deficiency Anemia (IDA).Objective: To compare the effect of weekly iron/folate vs standard daily iron/folate supplementation in pregnant women on compliance and hemoglobin level.Methods: The study was a quasi-experimental, non-equivalent control group design. Pregnant women with 20-28 week gestation were enrolled in this study in Bantul District. They were divided into two groups. One group (n=70), in Pajangan and Sewon Sub District, was given 120 mg iron/0,50 mg folate once a week, and the second group (n=65), in Bambang Lipuro and Pundong Sub District, received 60 mg iron/0,25 mg folate per day. Compliance with supplementation was assessed by the women self-reporting, pill count, and stool test. To measure hemoglobin level, the cyanmethemoglobin method was conducted.Results: Compliance was significantly higher in the weekly group (84.69% compared with 71.94%, p=0,004). A multiple logistic regression analysis indicated odds ratio 6.605, it means that in the weekly group compliance was 6,6 times higher than in the daily group. Hemoglobin level increased in both groups. There was no significant difference between groups for changes in hemoglobin. Initial haemoglobin values for the weekly (m=11.61 g/dl) and daily (m=11.27 g/dl) groups as well as final hemoglobin values (11.99 g/dl and 11.83 g/dl, respectively) did not differ significantly between the two groups.Conclusion: Supplementation on a weekly basis is as effective as daily supplementation in improving iron status in pregnant women. In the weekly group, compliance can be ensured.